Demonstration of an eye-movement-induced visual motion illusion (Filehne illusion) in Rhesus monkeys - Dash, S.; Dicke, P. W.; Chakraborty, S.; Haarmeier, T.; Thier, P. (Journal of vision (Charlottesville, Va.), 2009)
During pursuit eye movements, the world around us remains perceptually stable despite the retinal-image slip induced by the eye movement. It is commonly held that this perceptual invariance is achieved by subtracting an internal reference signal, reflecting the eye movement, from the retinal motion signal. However, if the reference signal is too small or too large, a false eye-movement-induced motion of the external world, the Filehne illusion (FI), will be perceived. A reference signal of inadequate size can be simulated experimentally by asking human subjects to pursue a target across backgrounds with externally added motion that are perceived as moving. In the present study we asked if non-human primates respond to such manipulation in a way comparable to humans. Using psychophysical methods, we demonstrate that Rhesus monkeys do indeed experience a percept of pursuit-induced background motion. In this study we show that an FI can be predictably induced in Rhesus monkeys. The monkey FI shows dependencies on the size and direction of background movement, which is very similar to the ones characterizing the human FI. This congruence suggests that the perception of self-induced visual motion is based on similar inferential mechanisms in non-human and human primates.